3D-printed pediatric endoscopic ear surgery simulator for surgical training. (November 2016) - Barber, Samuel R.; Kozin, Elliott D.; Dedmon, Matthew; Lin, Brian M.; Lee, Kyuwon; Sinha, Sumi; Black, Nicole; Remenschneider, Aaron K.; Lee, Daniel J.
Abstract: Introduction: Surgical simulators are designed to improve operative skills and patient safety. Transcanal Endoscopic Ear Surgery (TEES) is a relatively new surgical approach with a slow learning curve due to one-handed dissection. A reusable and customizable 3-dimensional (3D)-printed endoscopic ear surgery simulator may facilitate the development of surgical skills with high fidelity and low cost. Herein, we aim to design, fabricate, and test a low-cost and reusable 3D-printed TEES simulator. Methods: The TEES simulator was designed in computer-aided design (CAD) software using anatomic measurements taken from anthropometric studies. Cross sections from external auditory canal samples were traced as vectors and serially combined into a mesh construct. A modified tympanic cavity with a modular testing platform for simulator tasks was incorporated. Components were fabricated using calcium sulfate hemihydrate powder and multiple colored infiltrants via a commercial inkjet 3D-printing service. Results: All components of a left-sided ear were printed to scale. Six right-handed trainees completed three trials each. Mean trial time (n = 3) ranged from 23.03 to 62.77 s using the dominant hand for all dissection. Statistically significant differences between first and last completion time with the dominant hand (p < 0.05) and average completion time for junior and senior residents (p < 0.05) suggest construct validity. Conclusions: A 3D-printed simulator is feasible for TEES simulation. Otolaryngology training programs with access to a 3D printer may readily fabricate a TEES simulator, resulting in inexpensive yet high-fidelity surgical simulation.